Pelatihan dan Pendampingan Pembuatan Video Pembelajaran Genetika SMA Menggunakan Aplikasi Gratis Dari Internet - Chumidach Roini; Iqbal Limatahu; Suparman Suparman (Peneliti.net, 2022)
This partnership activity aims to improve the ability of high school biology teachers to make genetics learning videos so that the material is easier for students to understand. Activities using socialization methods, material deepening, training and mentoring were carried out online and attended by 21 biology teachers who are members of the Ternate City High School Biology MGMP. Meanwhile, mentoring activities were carried out offline and attended by 13 peoples. The pretest results showed that 46.7% of participants did not know about various applications that can be downloaded for free from the internet to make genetics learning videos and 92.1% of participants had never made their own learning videos, but in the posttest 98.2% of participants understood the applications. the. At the end of the material deepening activity, it was discovered that the participants had understood the genetic concept of protein synthesis and cross-breeding and there were no misconceptions. In training activities, participants are trained on how to download free applications from the internet and how to operate these applications to create learning videos, including: creating images, selecting various features available on Canva, combining various images and videos, adding music, adding text, editing images. and sound. At the end of the mentoring activity, it was discovered that 78% of the participants had been able to make learning videos, while 22% of the learning videos produced had not been completed and could not be used for learning.